Influence of limited-creep feeding on pre and postweaning performance of spring born calves - Houghton, P.; Brazle, F.; Kuhl, Gerry L.; Schalles, B.; Zoellner, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two limited-creep feeding trials were conducted in Northwest and Southeast Kansas using spring-born, suckling calves to evaluate the effect of available forage supply on creep-fed calf performance. Energy vs. protein creep feeds were compared at each location. Creep feed intake was limited with salt to achieve an average daily intake of about 1.5 lb per head. Calves consuming the limited energy and protein creep feeds gained from 0.1 to 0.6 lb more per head daily preweaning, and required 2.3 to 7.6 lb of creep per lb of extra weaning weight. Postweaning gains of the noncreep-fed calves were .12 to .27 lb per day higher than those of creep-fed calves, suggesting some compensation by the control calves postweaning.
Keywords: Beef; Limited-creep feeding; Performance; Calves